Effects of a fungicide on pollen morphology and fertility of tomato (Lycopersicon esculentum Mill.) - Çali, Ilkay Öztürk (Bangladesh Journal of Botany, 2010)
Effects of Equation Pro (22.5% Famoxadone + 30% Cymoxanil), a fungicide widely used on tomatoes (Lycopersicon esculentum Mill.) grown in greenhouses in Turkey against Phytopthora infestans and Alternaria solani, were studied on the morphology and fertility of tomato pollens. The fungicide was applied to tomatoes grown in pots in a greenhouse at recommended dosage (0.4 g/l water) and double the recommended dosage (0.8 g/l water). At the recommended dosage of Equation Pro, pollens were affected but at double the recommended dose, fertility is decreased to 41% with morphological deformity and thinner wall layers. Key words: Fungicide; Lycopersicon esculentum; Pollen; Morphology; Fertility DOI: 10.3329/bjb.v38i1.5112 Bangladesh J. Bot. 38(1): 7-11, 2009 (June)